2012
DOI: 10.1186/2047-2994-1-34
|View full text |Cite
|
Sign up to set email alerts
|

Self-sampling is appropriate for detection of Staphylococcus aureus: a validation study

Abstract: BackgroundStudies frequently use nasal swabs to determine Staphylococcus aureus carriage. Self-sampling would be extremely useful in an outhospital research situation, but has not been studied in a healthy population. We studied the similarity of self-samples and investigator-samples in nares and pharynxes of healthy study subjects (hospital staff) in the Netherlands.MethodsOne hundred and five nursing personnel members were sampled 4 times in random order after viewing an instruction paper: 1) nasal self-samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…This is however believed to be a minor bias. A recent pilot study has shown high degree of agreement between self-samples and investigator samples (93% agreement, κ 0.85 for nasal swabs and 83% agreement, κ 0.60 for throat swabs) 35. Another limitation is the previously described underestimation of MSSA presence but this is of negligible impact in the results because detection of MRSA and S aureus remains unaffected.…”
Section: Discussionmentioning
confidence: 96%
“…This is however believed to be a minor bias. A recent pilot study has shown high degree of agreement between self-samples and investigator samples (93% agreement, κ 0.85 for nasal swabs and 83% agreement, κ 0.60 for throat swabs) 35. Another limitation is the previously described underestimation of MSSA presence but this is of negligible impact in the results because detection of MRSA and S aureus remains unaffected.…”
Section: Discussionmentioning
confidence: 96%
“…Firstly, participants were swabbed only in the nares, which likely missed some carriage even at the timepoints assayed 30,31 ; a recent study suggests that this may have particularly underestimated carriage in younger people 32 . However, swabbing of the nares enabled participant self-swabbing, which was vital for our study and was recently shown to have reasonable accuracy 33 . Secondly, the bi-monthly sampling interval may have missed some transient carriage.…”
Section: Discussionmentioning
confidence: 98%
“…There is growing evidence from large studies that self-swabbing is acceptable to study participants, but there is limited data on the accuracy of self-swabbing by patients 19, 20. One study compared investigator to participant swabs, but these study participants were nursing personnel, and may not have represented patients who are not healthcare professionals 21 . Further, it is unclear how accurately samples taken weeks before admission predict carriage at admission 17 …”
Section: Introductionmentioning
confidence: 99%